DNA aptamer AptERA 2 targets ERA from Staphylococcus aureus and limits GTP hydrolysis - Katherin Peñaranda; Nicolle Pereira; Orestis Savva; Dezemona Petrelli; Roberto Spurio; Rebecca M. Corrigan; Pohl Milon (Scientific Reports)
Abstract Ribosome assembly is a multistep process that ensures a functional ribosome structure. The molecular mechanism that ribosomeassociated GTPases (RAGTPases) use to enhance ribosome assembly accuracy remains largely to be elucidated. Here, we use systematic evolution of ligands by exponential enrichment (SELEX), followed by sequencing, comprehensive bioinformatics analysis, and biochemical characterization to identify aptamers that target the RA-GTPase ERA of Staphylococcus aureus. ELONA and thermophoresis assays show that the AptERA 2 interaction with ERA is in the 200 nM range of affinity, displays a high level of specificity, and depends on the target structure. Docking to ERA suggests that AptERA 2 interacts with the protein’s KH domain, consistent with the aptamer’s similarities with helix 45 of the 16S rRNA. AptERA 2 did interact with the isolated KH domain but did not bind to the ∆KH ERA nor to the similar RA-GTPase RbgA, which shares the GTPase core but lacks the KH domain, confirming that the aptamer recognizes and binds the KH domain of ERA. This interaction leads to a significant reduction of 30S-dependent GTP hydrolysis, indicative of allosteric modulation of the enzyme activity or limiting ERA binding or the KH domain interaction with the 3’ end of the 16S rRNA rather than directly blocking GTP binding. Altogether, this work highlights the versatility of aptamers as tools to understand the complex processes of ribosome biogenesis further, offering new insights into bacterial protein synthesis mechanisms.